1999
DOI: 10.1002/etc.5620181106
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible binding of biologically reduced 2,4,6‐trinitrotoluene to soil

Abstract: To analyze the fate of 2,4,6-trinitrotoluene (TNT) and its reduction products, a TNT-contaminated soil (350 mg TNT/ kg dry soil) was spiked with [ring-UL-14.C]TNT and treated in a laboratory slurry reactor. During an anaerobic/aerobic treatment, the total radioactivity measured in the supernatant and methanolic soil extracts decreased to 2 per cent. The decrease corresponded to an increase of strongly bound radioactivity to the soil. Throughout the whole treatment process, mineralization of TNT was not observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 32 publications
8
77
2
Order By: Relevance
“…Moreover, as proposed by Sunahara et al (1998), the analogous appearance of reduced metabolites in the well-described anaerobic and aerobic reductive (bio)transformation pathway of TNT (Blotevogel and Gorontzy, 2000) would re#ect a process of detoxi"cation of the TNT molecule, which is detectable by luminescent bacteria. These "ndings suggest the special suitability of luminescent bacteria assays as a screening tool to detect changes in soil toxicity in the context of bioremediation of TNT-contaminated soils, where reductive processes are expected to be of relevance Lenke et al, 1998;Achtnich et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as proposed by Sunahara et al (1998), the analogous appearance of reduced metabolites in the well-described anaerobic and aerobic reductive (bio)transformation pathway of TNT (Blotevogel and Gorontzy, 2000) would re#ect a process of detoxi"cation of the TNT molecule, which is detectable by luminescent bacteria. These "ndings suggest the special suitability of luminescent bacteria assays as a screening tool to detect changes in soil toxicity in the context of bioremediation of TNT-contaminated soils, where reductive processes are expected to be of relevance Lenke et al, 1998;Achtnich et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…While anaerobic treatment of TNT-contaminated soil allows for rapid removal of TNT, research has shown that high levels of reduced metabolites are typically produced during this approach, remediation of which may require a second aerobic degradation stage (Achtnich et al 1999). Ahmed & Hughes (2002), Wang et al (2002) and Lenke et al (1998) have shown that these reduced metabolites bind tightly to the humic substances in soil.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between LSC-measured and HPLC-measured concentrations and between target and HPLCmeasured concentrations indicate that a large fraction of the spiked compound was rapidly transformed to extractable compounds that were non-identifiable using HPLC (i.e, compounds other than TNT, ADNTs and DANTs) or became so strongly associated to sediment particles that they were non-solvent extractable. Highly reactive aminated transformation products of TNT, either formed due to transformation of the parent compound or directly spiked to the sediment, have been reported to form covalent bonds with organic molecules in soil or sediment particles, especially humic acids, as has been observed in soils (Achtnich et al, 1999;Thorn and Kennedy, 2002;Eriksson et al, 2004).…”
Section: Tablementioning
confidence: 95%